A STUDY ON THE BENEFITS, CHALLENGES, AND MATURITY OF INDUSTRY 4.0 - Nogueira, Raquel; Terazzi, Luis (Revista Interface Tecnológica, 2025)
This study analyzes the benefits, challenges, and maturity level of Industry 4.0 based on the reality of a large multinational company in the automotive rubber sector, located in the countryside of São Paulo, Brazil. Industry 4.0 represents the integration of advanced technologies such as the Internet of Things, Big Data, Artificial Intelligence, and cloud computing, which are transforming production processes and organizational dynamics. The aim is to understand how these technologies impact industrial operations by identifying progress, obstacles, and the stage of technological maturity. The adopted methodology is qualitative, based on a case study and semi-structured interviews conducted with three employees directly involved in the implementation of Industry 4.0. The results reveal gains in productivity, efficiency, and decision-making, but also highlight challenges such as resistance to change, the need for professional training, and high initial investments. It is concluded that, despite evident benefits, full integration of these technologies still requires time, as well as cultural and strategic adaptation. The technological maturity of the studied company is under development, with consistent progress, but with challenges yet to be overcome.
Keywords: Efficiency; technology.; Digital Transformation